Supplement to Frege’s Theorem and Foundations for Arithmetic
Proof that Q is Hereditary on the Natural Numbers
We want to prove the following claim:
HerOn(Q,N)
The proof of this claim appeals to the following Lemma (cf. Gg I, Theorem 149):
Nx&Precedes(y,x)→#[λzPrecedes+(z,y)]=#[λzPrecedes+(z,x)&z≠x]
(Proof of the Lemma on Predecessor+)
Intuitively, the Lemma on Predecessor+ tells us that if y precedes a number x, then #[λzz≤y] is identical to #[λzz≤x&z≠x].
Now to show HerOn(Q,N), we have to show:
∀n∀m[Precedes(n,m)→(Qn→Qm)]
If we replace ‘Q’ with its definition and simplify the result by λ-Conversion, then what we have to show is:
(Intuitively, we have to show that if n precedes m, then if n precedes the number of numbers less than or equal to n, then m precedes the number of numbers less than or equal to m.) So, let n and m be arbitrary numbers, so that we know Nn and Nm and assume both:
(A) Precedes(n,m)
(B) Precedes(n,#[λzPrecedes+(z,n)])
to show:
Precedes(m,#[λzPrecedes+(z,m)])
By the definition of Predecessor, we have to show that there is a concept F and object x such that:
(1) Fx
(2) #[λzPrecedes+(z,m)]=#F
(3) m=#[λuFu&u≠x]
We can demonstrate that there is an F and x for which (1), (2) and (3) hold if we pick F to be [λzPrecedes+(z,m)] and pick x to be m. We now establish (1), (2), and (3) for these choices.
To show that (1) holds, we have to show:
[λzPrecedes+(z,m)]m
But we know, from the definition of Precedes+, that Precedes+(m,m). So by abstraction using λ-Conversion, we are done.
To show that (2) holds, we need do no work, since our choice of F requires us to show:
#[λzPrecedes+(z,m)]=#[λzPrecedes+(z,m)],
which we know by the logic of identity.
To show (3) holds, we need to show:
(C) m=#[λuPrecedes+(u,m)&u≠m]
[Note that the λ-expression in the above has been simplified by applying λ-Conversion to the following (which, strictly speaking, is what results when you substitute our choice for F in (3)):
[λu[λzPrecedes+(z,m)]u&u≠m]
In what follows, we use the simplified version of this λ-expression.]
Now in virtue of (A), (B) and the functionality of Predecessor (the proof of which was left as an exercise in the subsection No Two Numbers Have the Same Successor in §5), we know m=#[λzPrecedes+(z,n)]. So, substituting for m in (C), we have to show:
#[λzPrecedes+(z,n)]=#[λuPrecedes+(u,m)&u≠m]
But we can demonstrate this by appealing to the Lemma on Predecessor+ mentioned at the outset. We may instantiate the variables x and y in that Lemma to m and n, respectively, yielding:
Since the consequent is what we had to show, we are done, for the conjuncts of the antecedent are things we assumed to be true at the beginning of our conditional proof.